PROCEDURE FOR EMPLOYER’S LIABILITY RISK INSURANCE AND ITS ACCOUNT: (On The Example Of Social İnfrastructure Organizations) - Ibragimov K.Sh (International Journal of Advanced Science and Technology, 2020)
The article scientifically and theoretically examines issues such as the employer’s risk of civil liability in social infrastructure organizations, the importance of risk assessment, accounting of compulsory insurance practices and the participation of insurance companies in these processes. Some problematic situations that may occur in practice are also illustrated using examples.